The Running Performance Decrement in Elite Hurling - Damien Young (Applied Sciences, 2020)
Since the COVID-19 restrictions, hurling games have been played in four quarters instead of two halves. This study described the decrement in running performance between quarters in elite hurling. GPS (10 Hz) were used to collect data from 48 players over 20 games during 2018–2020 season. Total distance (TD), high-speed running (HSR), high-metabolic-load distance (HMLD), sprint-distance, and number of sprints (N-sprints) between quarters were assessed. Greater TD was covered in Q1 than Q3 (Cohen’s d = 0.26). HSR and HMLD was greater in Q1 than Q2 (d = 0.45 and d = 0.55, respectively), Q3 (d = 0.34 and d = 44, respectively) and Q4 (d = 0.38 and d = 0.48, respectively). Sprint-distance and N-sprints were similar (p > 0.05) across quarters. All positions experienced a drop-off in at least one quarter (d = 0.43–1.46) in all metrics except midfielders’ TD and full-forwards’ HSR and HMLD. Sprint-distance and N-sprints were similar (p > 0.05) in each quarter for all positions. Following Q1, players were able to maintain their running performance. The current results can aid the timing of substitutions especially in positions where temporal decrements were observed.